STUDENT PROBLEMS IN ONLINE LEARNING: SOLUTIONS TO KEEP EDUCATION GOING ON - Dion Tira Erlangga (Journal of English Language Teaching and Learning, 2022)
The spread of the Covid-19 virus that has swept across the world has changed various aspects of human life, one of which is the change of learning process that commonly occurs face to face in the classroom become online learning. Online learning is chosen as the solution to keep teaching and learning during this pandemic and this is done by various levels of education starting from primary school, middle school, high school, to college levels. The existence of cases of learning difficulties experienced by students during the Covid-19 pandemic made students do not understand the subject matter delivered by the teacher. This study aimed to find out some solutions of students' problem in the online learning process. Participants in this study were 25 English education students from a private university in Bandar Lampung. The researcher distributed a close ended questionnaire of 9 questions in the form of Google to collect data, and used qualitative data to illustrate the results of the questionnaire in data findings. The results of the study show that there were some problems faced by students in online learning included (1) students difficult to understanding materials, (2) students encounter technical difficulties, (3) limited internet quota, (4) poor communication, and (5) learning becomes less effective. The solutions that researcher has found to overcome the problems are namely (1) teachers or lecturers must implement face to face class twice a week, (2) teachers should use platforms with simpler operations in online learning, (3) teachers or lecturers should provide a material that is interactive, dynamic and attractive and (4) the government must extend the quota assistance for students.